Mediatizing religion and extremism: Muslim women terrorist networks on social media - Ilyas Supena; M. Mudhofi M. Mudhofi; Ulin Nihayah; Farida Rachmawati (Islamic Communication Journal, 2026)
This research aims to examine the role of social media in connecting the phenomenon of Muslim women with the community of terrorism networks in the digital space. Phenomenological and interview approaches were used to analyze the linkages between social media, Muslim women, and terrorism networks. The findings of the study show that social media not only functions as a communication tool, but has developed into a new religious living space for Muslim women who form identities, social networks of terrorist communities, and religious authorities digitally. The media acts as a channel that connects individuals with radical propaganda directly. Language that packages extreme messages in a persuasive and authentic format, often combining religious postulates with symbolic visuals. The environment that creates online communities also reinforces radical identities and allows participants to become active content producers. This study contributes to the literature on digital religion by demonstrating that social media not only mediates religious expression but also actively reshapes religious authority and social relations within online radicalization networks. ***** Penelitian ini bertujuan untuk mengkaji peran media sosial dalam menghubungkan fenomena perempuan Muslim dengan komunitas jaringan terorisme di ruang digital. Pendekatan fenomenologis dan wawancara digunakan untuk menganalisis keterkaitan antara media sosial, perempuan Muslim, dan jaringan terorisme. Temuan penelitian menunjukkan bahwa media sosial tidak hanya berfungsi sebagai alat komunikasi, tetapi telah berkembang menjadi ruang kehidupan keagamaan baru bagi perempuan Muslim dalam membentuk identitas, jaringan sosial komunitas teroris, serta otoritas keagamaan secara digital. Media ini berperan sebagai saluran yang menghubungkan individu secara langsung dengan propaganda radikal. Bahasa yang mengemas pesan-pesan ekstrem dalam format yang persuasif dan autentik, sering kali memadukan dalil-dalil agama dengan visual yang sarat simbol. Lingkungan yang membentuk komunitas daring ini juga memperkuat identitas radikal serta memungkinkan para partisipan menjadi produsen konten yang aktif. Studi ini berkontribusi pada literatur agama digital dengan menunjukkan bahwa media sosial tidak hanya memediasi ekspresi keagamaan, tetapi juga secara aktif membentuk ulang otoritas keagamaan dan relasi sosial dalam jaringan radikalisasi daring.